Analisis Kualitas Website Dinas Kesehatan Provinsi Kalimantan Barat Menggunakan Metode E-GovQual dan Importance Performance Analysis (IPA) - Rizqi Firdhani Muthmainah; Dian Prawira; Ilhamsyah Ilhamsyah (Jurnal Tekno Kompak, 2023)
Presidential Instruction No.3 Year 2003 on National Policy and Strategy for E-Government Development is being put into action via the creation of websites for Indonesian local governments. West Kalimantan Provincial Health Office is the organization that puts e-Government into practice. The West Kalimantan Provincial Health Office website serves to provide information about the profile and publication of data and public services from the West Kalimantan Provincial Health Office. However, in using the website, not all citizens as users have a good assessment of the website, including complaint services by the website manager who are less responsive, then loading the website takes a very long time when accessed so that users feel ineffective and hesitate to return to accessing the website. From these problems, an assessment of the quality of the website is very important to do. The method used in this research is E-GovQual and Importance Performance Analysis (IPA). As for the results of the performance level questionnaire with an average value of 3.57 and the level of importance with an average value of 4.11. The average value of the conformity level is 87% and the average value of the gap level (Gap) is -0.54, which means which means the service quality of the West Kalimantan Provincial Health Service website is still not good. Based on the results of the IPA quadrant mapping analysis, indicators in quadrant I were obtained which were the main focus of improvement, namely the variables Realibility and Citizen Support.Keywords: Website, Quality, E-GovQual, e-Government, Importance Performance Analysis (IPA).